Law on HIV/AIDS prevention and control - The National Assembly (2006)
This Law provides for HIV/AIDS prevention and control measures; the care, treatment and support for HIV-infected people and conditions for the implementation of HIV/AIDS prevention and control measures. Law applies to Vietnamese and foreign agencies, organizations and individuals in Vietnam.